2009
DOI: 10.1186/1742-4755-6-18
|View full text |Cite
|
Sign up to set email alerts
|

WHO Global Survey on Maternal and Perinatal Health in Latin America: classifying caesarean sections

Abstract: BackgroundCaesarean section rates continue to increase worldwide with uncertain medical consequences. Auditing and analysing caesarean section rates and other perinatal outcomes in a reliable and continuous manner is critical for understanding reasons caesarean section changes over time.MethodsWe analyzed data on 97,095 women delivering in 120 facilities in 8 countries, collected as part of the 2004-2005 Global Survey on Maternal and Perinatal Health in Latin America. The objective of this analysis was to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
8
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 15 publications
13
89
8
15
Order By: Relevance
“…The rate of caesarean section in this group (20.5%) is higher than those observed by Betrán et al [12] and Kelly et al [4], who found 12.6% and 13.19% respectively in Latin America and Canada. This difference could be put down to the fact that these are highly medicalized countries and the figures come from statistics at the country and continent levels.…”
Section: K Achille Et Al Open Journal Of Obstetrics and Gynecologycontrasting
confidence: 54%
“…The rate of caesarean section in this group (20.5%) is higher than those observed by Betrán et al [12] and Kelly et al [4], who found 12.6% and 13.19% respectively in Latin America and Canada. This difference could be put down to the fact that these are highly medicalized countries and the figures come from statistics at the country and continent levels.…”
Section: K Achille Et Al Open Journal Of Obstetrics and Gynecologycontrasting
confidence: 54%
“…The risk of cesarean section (CS) in nulliparous women with spontaneous start of labor, cephalic presentation, and no previous scar has been reported to be 2.5 times higher than for comparable parous women (15). The reason why nulliparous women carry higher risks is not fully understood even though it has been known for more than 40 years (16,17).…”
Section: Introductionmentioning
confidence: 96%
“…WHO global survey on maternal and perinatal health in Latin America, in fact, unveiled that rate of caesarean delivery was positively associated with severe maternal and neonatal morbidity and mortality, even after adjustment of demographic characteristics, risk factors, type of institution and proportion of referrals. 1 Also, unneeded caesareans beget higher expenditure at individual and national levels and have the potential to divert human and financial resources. In spite of these facts, CS is high and continues to hike in the developed world and in many developing countries.…”
Section: Introductionmentioning
confidence: 99%